Effectiveness of Using Virtual Laboratory PhET in Thermodynamics Learning to Improve Students' Learning Outcomes - Rambe, Ismail Saleh; M. Nor, M. Nor (Journal of Indonesian Science Teachers, 2025)
Physics learning often faces challenges in understanding abstract concepts, such as thermodynamics, which require visualization and experimentation to enhance students' understanding. However, limited laboratory facilities in many schools pose a significant obstacle. This study aims to examine the effectiveness of using PhET virtual laboratories in thermodynamics learning to improve the learning outcomes of 11th-grade high school students. The study employed a quasi-experimental method with a posttest-only control group design. The subjects were students of SMA Negeri 5 Pekanbaru, consisting of two classes: an experimental class using the PhET virtual laboratory and a control class applying conventional teaching methods. The instrument used was a learning outcome test. The results showed that the average learning outcomes of students in the experimental class significantly improved compared to the control class. The use of the PhET virtual laboratory helped students to understand thermodynamics concepts more deeply through interactive simulations. Students' responses to learning with PhET were also very positive, as it was considered engaging, easy to use, and relevant to the taught concepts. The study concludes that the PhET virtual laboratory is effective in thermodynamics learning to improve students' learning outcomes, providing a more meaningful and enjoyable learning experience.